Medicinal Plants in the Treatment of Hypertension: A Review - Raha Kamyab; Hossein Namdar; Mohammadali Torbati; Morteza Ghojazadeh; Mostafa Araj-Khodaei; Seyyed Mohammad Bagher Fazljou (Tabriz University of Medical Sciences, 2021)
Traditional medicine is a comprehensive term for ancient, culture-bound health care practices that existed before the use of science in health matters and has been used for centuries. Medicinal plants are used to treat patients with cardiovascular diseases, which may occur due to ailments of the heart and blood vessels and comprise heart attacks, cerebrovascular diseases, hypertension, and heart failure. Hypertension causes difficulty in the functioning of the heart and is involved in atherosclerosis, raising the risk of heart attack and stroke. Many drugs are available for managing these diseases, though common antihypertensive drugs are generally accompanied by many side effects. Medicinal herbs have several active substances with pharmacological and prophylactic properties that can be used in the treatment of hypertension. This review presents an overview of some medicinal plants that have been shown to have hypotensive or antihypertensive properties.